Pengelolaan Pembelajaran Praktek Kerja Industri Kompetensi Keahlian Seni Karawitan (Studi Kasus di SMK Negeri 8 Surakarta) - Surono, Surono, Dr. Suyatmini, M.Si, Dr. Sabar Narimo, M.M., M.Pd (2015)
Surono, Learning Management Practice Industrial Work Skills Competency Karawitan Art (Case Study in SMK Negeri 8 Surakarta), Thesis, Master of Education Management, Graduate Program, University of Muhammadiyah Surakarta. The study had three objectives, namely to analyze and describe about: 1) Learning Management planning Prakerin and meaning DU / DI, 2) Implementation Prakerin and Learning Process Management implementation, and 3) Form of Learning Management Prakerin evaluation. This study used descriptive qualitative approach. The study design using the design case studies. Object of research are the characteristics and learning management expertise Competence Prakerin Karawitan Art. Data in the form of primary data and secondary data from a data source interviews and related documents. Data analysis techniques with interactive model. The validity of the data using triangulation techniques. Results of research learning management Prakerin Skill Competency Art Karawitan are: Management of Learning Prakerin begins with the determination of strategy and planning include: Establishment of Committees and Preparation Schedule, b) Determination of the cooperation agreement dengaan DU / DI: Making of DU / DI, c) Preparation of Material gendhing, d ) Briefing and division of the group, e) Preparation Financing Plan. Prakerin implementation include: 1) Implementation Prakerin, 2) the implementation process include: a) exploratory phase material, b) Phase mentoring works and manuscripts, c) Implementation Phase Competency Test. Assessment include: a) assessment process, b) Assessment Competency Test, c) assessment manuscript. Prakerin assessment aims to determine the ability to master the material in the context of the work on the piece Semarangan be able to practice the skills and able to describe in the realm of science.